Contemporary rates and predictors of open conversion during minimally invasive partial nephrectomy for kidney cancer. (March 2021) - Luzzago, Stefano; Rosiello, Giuseppe; Pecoraro, Angela; Deuker, Marina; Stolzenbach, Franziska; Mistretta, Francesco Alessandro; Tian, Zhe; Musi, Gennaro; Montanari, Emanuele; Shariat, Shahrokh F.; Saad, Fred; Briganti, Alberto; et al.
Abstract: Objectives: To test contemporary rates and predictors of open conversion at minimally invasive partial nephrectomy (MIPN: laparoscopic or robotic partial nephrectomy). Materials and methods: Within the National Inpatient Sample database (2008–2015) we identified all MIPN patients and patients that underwent open conversion at MIPN. First, estimated annual percentage changes (EAPC) tested temporal trends of open conversion. Second, univariable and multivariable logistic regression models predicted open conversion at MIPN. All models were weighted and adjusted for clustering, as well as all available patient and hospital characteristics. Results: Of 7649 MIPN patients, 287 (3.8%) underwent open conversion. The rates of open conversion decreased over time (from 12 to 2.4%; EAPC: 24.8%; p = 0.004). In multivariable logistic regression models predicting open conversion, patient obesity achieved independent predictor status (OR:1.80; p < 0.001). Moreover, compared to high volume hospitals, medium volume (OR:1.48; p = 0.02) and low volume hospitals (OR:2.11; p < 0.001) were associated with higher rates of open conversion. Last but not least, when the effect of obesity was tested according to hospital volume, the rates of open conversion ranged from 2.2 (non obese patients treated at high volume hospitals) to 9.8% (obese patients treated at low volume hospitals). Conclusion: Overall contemporary (2008–2015) rate of open conversion at MIPN was 3.8% and it was strongly associated with patient obesity and hospital surgical volume. In consequence, these two parameters should be taken into account during preoperative patients counselling, as well as in clinical and administrative decision making. Highlights: The rates of open conversion at MIPN is 3.8%. The rates of open conversion at MIPN are decreasing. Obesity and Hospital Volume are associated with open conversion rates at MIPN.